Dynamic Radiation Effects Induced by Short-Pulsed GeV U-Ion Beams in Graphite and h-BN Targets. (18th September 2021) - Bolz, Philipp; Drechsel, Philipp; Prosvetov, Alexey; Simon, Pascal; Trautmann, Christina; Tomut, Marilena
Abstract : Targets of isotropic graphite and hexagonal boron nitride were exposed to short pulses of uranium ions with ∼1 GeV kinetic energy. The deposited power density of ∼3 MW/cm³ generates thermal stress in the samples leading to pressure waves. The velocity of the respective motion of the target surface was measured by laser Doppler vibrometry. The bending modes are identified as the dominant components in the velocity signal recorded as a function of time. With accumulated radiation damage, the bending mode frequency shifts towards higher values. Based on this shift, Young's modulus of irradiated isotropic graphite is determined by comparison with ANSYS simulations. The increase of Young's modulus up to 3 times the pristine value for the highest accumulated fluence of 3 × 10 13 ions/cm 2 is attributed to the beam-induced microstructural evolution into a disordered structure similar to glassy carbon. Young's modulus values deduced from microindentation measurements are similar, confirming the validity of the method. Beam-induced stress waves remain in the elastic regime, and no large-scale damage can be observed in graphite. Hexagonal boron nitride shows lower radiation resistance. Circular cracks are generated already at low fluences, risking material failure when applied in high-dose environment.